Material de referência para organização, orientação e avaliação de feiras de ciências escolares - Rafael Parreira Silva (2018)
This work presents the elaboration of an educational product that approaches strategies of orientation and evaluation of science fairs. We reflect on the ways of conducting a science fair that consider the production of the student during the research and that are not only linked to the presentation of results or even to the implementation of the "steps" of the scientific method. We present a model of organization of science fairs such as school projects, produced in partnership with PIBID-Physics-FaE, proposing the use of guidance strategies such as logbook, research question, project summary, final report and evaluation participatory approach. We conducted a research with high school students of a state public school with the objective of reflecting on their expectations regarding the project of the science fair, in addition to researching which orientation strategies are most used by them and their teachers throughout a science fair. For this research we elaborated a questionnaire submitted to the students and analyzed the results by digital means. A previous version of the product was presented to experienced teachers and researchers for analysis to gather criticisms and suggestions that would enhance the product. In the development, we seek to adapt its format and design, making it more attractive to its target audience - teachers of basic education. With the pertinent theoretical references, the model of organization of science fairs elaborated, the research carried out, the critical analysis of teachers and researchers and the graphic design of the text, we arrived at a final version of the educational product, entitled "School science fairs: Teacher support material ". In the future, we hope to have the opportunity to effectively use the educational product in a school context and distribute it to the interested teachers, as well as to include the product as support material in continuing teacher training courses.